2011
DOI: 10.1007/s00455-011-9362-0
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Immobility and Aspiration Status: A Direct Replication Study

Abstract: The purpose of this direct replication study was to confirm the incidence of vocal fold immobility (VFI) and its relationship to pharyngeal dysphagia and aspiration. Using a single-group consecutively referred case series, a total of 2,650 participants underwent fiberoptic endoscopic evaluation of swallowing between August 2003 and December 2007. Main outcome measures included overall incidence of VFI and aspiration status, with specific emphasis on age, gender, etiology and pharyngeal phase bolus flow charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…The percentage of aspiration in this study was also comparable to previous studies, which identified aspiration in approximately 33% to 42% of individuals with UVFI . It is important to note that the present study was performed in an outpatient tertiary care center and most of the previous work evaluating aspiration in patients with UVFI was performed in acute care settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The percentage of aspiration in this study was also comparable to previous studies, which identified aspiration in approximately 33% to 42% of individuals with UVFI . It is important to note that the present study was performed in an outpatient tertiary care center and most of the previous work evaluating aspiration in patients with UVFI was performed in acute care settings.…”
Section: Discussionsupporting
confidence: 88%
“…If airway protection is ineffective, an individual may aspirate material into the lungs, which may result in respiratory infection and/or death due to aspiration pneumonia. Approximately 33% to 42% of individuals with UVFI have been identified to aspirate . Diminished airway protection is presumed to be the primary cause of swallowing dysfunction in patients with UVFI .…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of clinical observations which suggest that a long‐term link may exist between vocal palsy and aspiration and whilst our study does not prove causality, but our findings are consistent with what is known of the physiology of the larynx and in particular, over‐reliance of the human swallowing mechanism on fine neurological control and thus its particular susceptibility to neuromuscular dysfunction . The incidence of laryngeal nerve injury in patients undergoing oesophagectomy and thoracic aortic surgery is 20%‐40%, and in these patients, it is known that post‐operative vocal palsy significantly increases the risk of hospital‐acquired pneumonia and length of stay .…”
Section: Discussionsupporting
confidence: 80%
“…The primary function of the larynx is sphincteric protection of the airway against ingress of digestive tract contents, and the principal mechanism by which this is achieved is reflexive closure of the true vocal folds during swallowing . Vocal palsy impairs glottic closure, and this is known to lead to dysphagia and aspiration in 20%‐40% of the affected patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation